PD‐L1 and PD‐L2 expression status in relation to chemotherapy in primary and metastatic esophageal squamous cell carcinoma. Issue 2 (8th December 2021) - Okadome, Kazuo; Baba, Yoshifumi; Yasuda‐Yoshihara, Noriko; Nomoto, Daichi; Yagi, Taisuke; Toihata, Tasuku; Ogawa, Katsuhiro; Sawayama, Hiroshi; Ishimoto, Takatsugu; Iwatsuki, Masaaki; Iwagami, Shiro; Miyamoto, Yuji; et al.
Abstract: Immune checkpoint inhibitors have shown efficacy in various cancers. Although programmed death ligand 1/2 (PD‐L1/L2) expressions have been demonstrated as predictive biomarkers of response to immune checkpoint inhibitors and prognostic markers, whether PD‐L1/L2 expression is altered in esophageal squamous cell carcinoma during the therapeutic course is unclear. Whether PD‐L1/L2 expression in metastatic or recurrent lesions is consistent with that in primary tumors is also unknown. This study included 561 surgically resected esophageal squamous cell carcinomas and PD‐L1/L2 expression was evaluated by immunohistochemistry. We investigated the influence of chemotherapeutic drugs (cisplatin and fluorouracil) on PD‐L1/L2 expression and PD‐L1/L2‐related pathways in vitro. We also examined PD‐L1/L2 expression in 18 surgically resected lymph node metastases and 10 recurrent lesions compared with primary lesions. The positive rate of PD‐L1 was significantly higher in patients with preoperative chemotherapy than in those without preoperative therapy. The positive rate of PD‐L2 expression showed no significant difference between patient groups. Cisplatin increased PD‐L1 expression in cancer cell lines in vitro, but decreased PD‐L2 in some cell lines. The effects of cisplatin on phosphorylated signal transducer and activator of transcription 1/3 (pSTAT1/3) also differed depending on cell lines. Fluorouracil increased PD‐L1 and PD‐L2 expression. PD‐L1/L2 expression in lymph node metastases and recurrent lesions did not always match expression in primary lesions. PD‐L1/L2 expression may be altered by preoperative chemotherapy, and PD‐L1 /L2 expression in primary lesions does not always match that of metastatic/recurrent lesions. Thus, one‐time evaluation is not sufficient to evaluate PD‐L1/L2 expression as a biomarker in esophageal cancer. Abstract : The positive rate of programmed death ligand 1 (PD‐L1) was higher in patients who received preoperative chemotherapy or chemoradiotherapy than in patients who did not receive preoperative therapy. The positive rate of programmed death ligand 2 (PD‐L2) was not significantly different among the three groups. These results suggest that PD‐L1 expression may be increased by preoperative chemotherapy, but PD‐L2 expression is not necessarily increased.